2009
DOI: 10.1021/ed086p600
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Myoglobin Stability by Circular Dichroism Spectroscopy: Classic and Modern Data Analysis

Abstract: Few laboratory procedures describe the use of circular dichroism (CD) at the undergraduate level. To increase the number of laboratory exercises using CD, a thermal denaturation study of myoglobin using CD is described to assess protein stability. Values obtained from a more classic linear data analysis approach are consistent with data analyzed with a modern software program that "fits" the data set to a model using a non-linear approach. Both methods gave quantities consistent with reported literature values. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 4 publications
1
26
0
3
Order By: Relevance
“…Thermodynamic stability parameters of HepI-WT and mutants were calculated as previously reported by Mehl et.al, using ellipticities at 211 and 222 nm (Supplemental Table S3). 20 Percent composition of secondary structure (α-helicity and β-strand percentages) was determined using the K2D3 CD spectral analysis tool (http://cbdm-01.zdv.uni-mainz.de/~andrade/k2d3//info/about.html). …”
Section: Methodsmentioning
confidence: 99%
“…Thermodynamic stability parameters of HepI-WT and mutants were calculated as previously reported by Mehl et.al, using ellipticities at 211 and 222 nm (Supplemental Table S3). 20 Percent composition of secondary structure (α-helicity and β-strand percentages) was determined using the K2D3 CD spectral analysis tool (http://cbdm-01.zdv.uni-mainz.de/~andrade/k2d3//info/about.html). …”
Section: Methodsmentioning
confidence: 99%
“…At physiological conditions, HoloMb is stable by typically 45–55 kJ/mol (with higher stability observed for Mbs of diving mammals [12] , [13] ). It unfolds with a barrier of ∼45 kJ/mol (horse Mb) [14] with T m ∼80–85°C [11] , a process that, in contrast to many other small, single-domain proteins that fold by two-state processes [15] , may involve several intermediates (I) between the native (N) and unfolded (U) states [16] . Loss of heme takes days under physiological conditions due to the very high protein-heme affinity [17] , with a rate of heme loss of ∼0.01 h −1 [18] .…”
Section: Introductionmentioning
confidence: 99%
“…Figure 8 shows the CD spectra of commercial and extracted myoglobin from human serum. As can be seen from the figure, bands between 190 and 230 nm show the α -helical type of secondary structure of 500 mg/mL myoglobin (blue spectrum) [ 44 , 45 ]. The red spectrum showed that α -helical type of secondary structure in 208-222 nm interval remained for isolated myoglobin.…”
Section: Resultsmentioning
confidence: 99%